Analysis of the Tsunami of December 26, 2004, on the Kerala Coast of India - Part II: Arrival Times - M. Baba N. P. Kurian B. T. Murali Krishnan N. Nirupama T. S. Murty (Marine Geodesy, 29: 271-276, 2006, 2006)
The Tsunami of December 26, 2004, in the Indian Ocean arrived on the coast of Kerala in southwest India some three hours after the tsunami was generated. The tsunami activity persisted throughout that day and, in some locations, even into the early morning of the next day. Based on interviews with eye witnesses, arrival times of tsunami waves are presented here followed by some preliminary analysis of the results.